2019
DOI: 10.3389/fimmu.2019.00313
|View full text |Cite
|
Sign up to set email alerts
|

Variability in German Cockroach Extract Composition Greatly Impacts T Cell Potency in Cockroach-Allergic Donors

Abstract: German cockroach extract is used clinically to evaluate allergen-specific sensitization and for subcutaneous allergen-specific immunotherapy, though there are no guidelines for standardization in its manufacture. We performed an immunological evaluation of 12 different cockroach extracts prepared from different sources and their potency to induce allergen-specific T cell reactivity. PBMC from 13 cockroach allergic donors were expanded in vitro with 12 different German cockroach extracts. After culture expansio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

6
2

Authors

Journals

citations
Cited by 21 publications
(39 citation statements)
references
References 26 publications
1
38
0
Order By: Relevance
“…After 14 days in culture with the BP lysate, the expanded T cells were tested for the recognition of the epitope pools or individual peptides as described above. As readout, the standard IFNγ/IL-5 and IL-17/IL-9 cytokine combination for ELISpot assay or IFNγ/IL-5/IL-13 cytokine combination for FluoroSpot assay was performed as described [9,34]. For ex vivo determinations, the same combination of cytokines was used after 20 h incubation with lysate (10 μg/mL), epitope pools (2 μg/mL), or individual peptides (10 μg/mL) besides PHA (2 μg/mL) and DMSO as positive and negative controls, respectively.…”
Section: Pbmc Isolationmentioning
confidence: 99%
“…After 14 days in culture with the BP lysate, the expanded T cells were tested for the recognition of the epitope pools or individual peptides as described above. As readout, the standard IFNγ/IL-5 and IL-17/IL-9 cytokine combination for ELISpot assay or IFNγ/IL-5/IL-13 cytokine combination for FluoroSpot assay was performed as described [9,34]. For ex vivo determinations, the same combination of cytokines was used after 20 h incubation with lysate (10 μg/mL), epitope pools (2 μg/mL), or individual peptides (10 μg/mL) besides PHA (2 μg/mL) and DMSO as positive and negative controls, respectively.…”
Section: Pbmc Isolationmentioning
confidence: 99%
“…It has to be highlighted that in this study, we have only tested one batch per food extract. Variability in extract content has been reported for commercial extracts [25,35,36] and it is likely that reactivity reported herein will vary further when different extract batches are tested.…”
Section: Discussionmentioning
confidence: 95%
“…IL-5 and IFNγ production after CM and CM-containing food extract stimulation was measured by Fluorospot assay as described in another study [25]. In vitro expanded cells (1 × 10 5 cells/well) were restimulated with the same extract as the original culture at 250 µg/mL, medium alone and PHA (10 µg/mL) as negative and positive controls, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…Conventional whole‐body GCr allergen source materials used by US manufacturers contain male and female insects, egg cases and faeces. Our analysis confirms 7 that the specific allergen content of a GCr allergen extract will depend on the relative proportions of these specific components. Extracts derived from source materials rich in faeces will contain more Bla g 1 and Bla g 11, whereas extracts from adult male whole bodies and adult female whole bodies/eggs will contain more Bla g 4 and vitellogenin, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…German cockroach (GCr; Blattella germanica ) is an indoor pest and important source of allergens associated with asthma and allergic rhinoconjunctivitis 5 . Commercial allergen extracts for GCr are non‐standardized, and several studies have confirmed low biological potency and a lack of consistency among products manufactured by different companies 6,7 . Further, although 10 GCr allergens have been identified (http://www.allergen.org), none of them is immunodominant 8,9 …”
Section: Introductionmentioning
confidence: 99%